Analisis Materi Menyimak Bahasa Prancis Tingkat A1 pada Platform Memrise - Lauranisa Andramaya; Dadang Sunendar; Iis Sopiawati (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
Listening skills are an important basic skill in French language learning, especially for beginners at the A1 level. This study aims to analyze the suitability of French listening materials on the Memrise platform with CECRL indicators. The method used is descriptive qualitative through documentation and content analysis techniques. The sample was selected purposively based on relevance to the CECRL Level A1 indicators. The analysis results indicate that the eight contents examined represent all listening indicators at the A1 level. The materials are presented contextually, with audiovisual support and clear pronunciation by native speakers. These findings suggest that Memrise can be used as an alternative learning medium to support the mastery of basic French listening skills.